Catching up and falling behind: Cross-country evidence on the impact of the EU ETS on firm productivity - Michael Themann; Nicolas Koch (RWI - Leibniz-Institut für Wirtschaftsforschung, 2021)
This paper assesses the potential impact of the European Union Emissions Trading System (EU ETS) on firm productivity. We estimate a stylized version of the neo-Schumpeterian model, which incorporates innovation and productivity catch-up as two potential sources of firm's productivity growth, while at the same time accounting for persistent productivity dispersion within industries. This dynamic model allows us to differentiate the potential effects of the EU ETS on total factor productivity (TFP) depending on the level of firms' technological advancement. The identification approach is based on a difference-in-difference approach exploiting the incomplete participation requirements of the EU ETS and the rich panel structure of firm-level data for eight EU countries from 2002 to 2012. We find evidence that the policy effects on TFP are highly heterogeneous and depend on the distance to the technological frontier, measured as the highest TFP in each year-industry. Productivity effects are positive for firms that are close to the frontier, but they turn negative for firms operating far behind the frontier. – – In dieser Studie untersuchen wir die möglichen Auswirkungen des Emissionshandelssystems der Europäischen Union (EU ETS) auf das Produktivitätswachstum der regulierten Firmen. Auf Basis von Firmen-Paneldaten für 8 EU-Länder für den Zeitraum von 2002-2012 und unter Verwendung eines Differenz-in-Differenzen-Ansatzes wird der Effekt dieser Politikmaßnahme geschätzt. Wir verwenden eine stilisierte Version des neo-schumpeterianischen Modells, welches Innovation und den technologischen Aufholprozess als zwei potenzielle Quellen für Produktivitätswachstum beinhaltet und die Produktivitätsstreuung innerhalb der Wirtschaftsbranchen berücksichtigt. Ein zentrales und robustes Ergebnis dieser Analyse sind die heterogenen Auswirkungen des ETS: Das System hat positive Effekte für die effizientesten Unternehmen, aber negative Effekte für Unternehmen, die weit von der Effizienzgrenze entfernt sind. Dieses Ergebnis stützt beide Paradigmen, die in Bezug auf die Auswirkungen von Umweltregulierung vorherrschen: die Porter-Hypothese, nach der Umweltregulierung bei Firmen zu Effizienzgewinnen führt, wie dies beim ETS für die effizientesten Firmen der Fall zu sein scheint, und die konträre konventionelle Sichtweise, nach der Umweltregulierung zu Effizienzverlusten führen kann.
Keywords: D22; Q54; Q58; 330; Environmental regulation; EU ETS; productivity; competitiveness